Simultaneous Determination of Ciprofloxacin Hydrochloride and Mebeverin Hydrochloride by Derivative Spectrophotometry - Mohammmed, Maha A.; Kadhum, Muna A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A new Spectrophotometric method, is for individual and simultaneous determination of Ciprofloxacin hydrochloride(CIP) and Mebeverin hydrochloride(MEB) by the first and second derivative mode techniques. The first and second derivative spectra of these compounds permitted individual and simultaneous determination of CIP and MEB in concentration range of (4-28Âµg/mL) by measuring the amplitude of peak- to- base line and the area under peak at selected spectrum intervals. The methods showed a reasonable precision and accuracy and have been applied to determine CIP and MEB in four different pharmaceutical preparations.